Effectiveness of housing design features in malaria prevention: architects’ perspective - Chisumbe, Sampa; Aigbavboa, Clinton; Akinradewo, Opeoluwa; Mukeya, Gideon (Frontiers in Built Environment, 2024)
Introduction: This research aimed to assess housing design consideration features and architects’ perceptions of their effectiveness in malaria prevention. Previous studies have highlighted various architectural design elements that can reduce mosquito entry into homes, thus contributing to malaria prevention. This study aims to build on these insights by evaluating specific design features and gathering professional opinions on their effectiveness. Methods: The methodological approach adopted was quantitative, with data collected using a structured questionnaire containing closed-ended questions and a checklist. The observation checklist was used to ascertain mosquito entry reduction features incorporated in 208 systematically selected houses in Garneton East, Kitwe, Zambia. Additionally, a structured questionnaire containing fourteen key design features identified from the literature was administered to 76 architects purposively sampled to establish their perceptions of the effectiveness of these design factors in malaria prevention. Data collected was analyzed using descriptive statistics and exploratory factor analysis. Results: The findings revealed that most houses needed to incorporate design features to reduce mosquito entry. The common features incorporated were ceilings (86.80%), screened air ventilation (59.80%), and window screens (54.40%). The use of window and door screens, as well as mosquito-repellent paint, were perceived as the most effective measures by the architects. Discussion: The results suggest a keen awareness among architects regarding the efficacy of certain design features in malaria prevention. Despite this awareness, the implementation of these features in actual housing designs needs to be improved. This indicates a need for greater effort and adaptation in building regulations to promote the use of mosquito entry reduction features. Enhancing housing designs with these features can significantly reduce malaria morbidity and mortality. Therefore, it is recommended that building regulations be updated to support and encourage the incorporation of mosquito entry reduction features in housing designs.